Use of the Internet as a prevention tool against cognitive decline in normal aging - Klimova B (Dove Medical Press, 2016)
Blanka Klimova Department of Applied Linguistics, Faculty of Informatics and Management, University of Hradec Kralove, Hradec Kralove, Czech Republic Abstract: Recent demographic trends indicate that older people appear to be one of the fastest growing population groups worldwide. In the year 2000, people older than 65 years represented 12.4% of the population. This number is expected to rise to 19% by 2030, particularly in developed countries. Therefore, there is sustained effort at both national and international levels to prolong the active life of these people as long as possible. Since the present older generation at the age of 55 years is already digitally literate, the use of technologies is one of the solutions. The purpose of this study is to discuss the role of the Internet in the prevention of cognitive decline in normal aging. The author examines clinical studies that exploit the use of the Internet, including online training programs, in the prevention of cognitive decline in healthy older individuals. The findings of the clinical studies indicate that the use of the Internet, especially online cognitive training programs, may have a positive effect on the improvement of cognitive functions in healthy older adults. Nevertheless, larger sample longitudinal randomized controlled clinical trials aimed at the prevention of cognitive decline among healthy older adults are needed. Keywords: healthy older individuals, Internet, prevention, cognitive functions, training